EXPERIENCES IN IMPLEMENTING CBDCs (World Economics and Finance Bulletin, 2024)
This article reveals statistical and analytical data on the trends and practices of central bank digital currencies abroad, and describes the risks and potential benefits for Central Asian countries.
Keywords: digital currency; CBDC; global GDP; stablecoins